Formulasi Ekstrak Buah Mengkudu (Morinda citrifolia) dalam Bentuk Sediaan Transdermal Liposome Cream - Amrianto Amrianto; Mukarramah Mukarramah; Dike Dandari Sukmana; Nurun Nahda; Andi Dian Permana (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2017)
Indonesia is a country rich in herbs. One of them is Noni (Morinda citrifolia). Noni fruit has good benefits for the body such as natural antioxidants and several other benefits. The use of noni fruit as herbal medicine is often used but the way make was still very inadequate to get the optimum effect on the plant. One effort that can be done is to make it a cream preparation liposomes that are used topically. Aims of this research was formulation of Transdermal liposome cream from noni fruit extract. The result showed that the total phenolic content of the extract of noni fruit was as much as 180 µg GAE/g ekstrak. The result of the evaluation of transdermal liposome cream preparation obtained both formulas have viscosity of 9,000 cps and 38.000 cps respectively, have uniform vesicle shape, high adsorption efficiency of 95% and 96,67%, but in formula 2 pH obtained did not fulfill the criteria of topical preparation, while formula 1 fulfilled the criterion that is 6,5. From these results it can be concluded that the noni fruit extract can be prepared in the form of transdermal cream preparations which have good physical characteristics achieved by formula 1.